Expression of osteogenic proteins in kidneys of cats with nephrocalcinosis - Nuttha Hengtrakul; Eva Furrow; Michael Borofsky; Ferenc Toth; Jody P. Lulich (Journal of Veterinary Internal Medicine)
Abstract Background Nephrocalcinosis is a common pathological finding in cats with chronic kidney disease and nephrolithiasis. Understanding its pathogenesis may identify future therapeutic targets. Hypothesis Nephrocalcinosis is associated with expression of an osteogenic phenotype. Animals Kidneys with medullary mineralization were obtained from 18 cats (10 with and 8 without nephroliths) undergoing necropsy. Methods Cross‐sectional study. Microradiography and histopathology (modified von Kossa stain) were used to confirm parenchymal mineralization. Immunohistochemistry for 5 osteogenic markers was performed to determine their co‐localization with nephrocalcinosis. The proportion of kidneys with stronger immunointensity in mineralized versus non‐mineralized regions was analyzed using 1‐tailed sign tests. The proportion of kidneys with co‐localization of nephrocalcinosis and each marker was compared between kidneys with and without nephroliths using Fisher's exact tests. Results Nephrocalcinosis co‐localized with osteopontin immunoreactivity in all 18 cats (100%) and with osteocalcin in 12 cats (67%). Both osteogenic markers had stronger immunointensity in mineralized regions compared with non‐mineralized regions. Limited co‐localization was observed with other markers: bone morphogenic protein‐2 in 2 kidneys (both with nephroliths) and tissue non‐specific alkaline phosphatase in 1 kidney (without nephroliths); runt‐related transcription factor‐2 was undetected. No statistically significant differences were found in the co‐localization of nephrocalcinosis with osteogenic proteins between kidneys with and without nephroliths. Conclusions and Clinical Importance Expression of osteogenic proteins in areas of nephrocalcinosis indicates that nephrocalcinosis is associated with the development of an osteogenic phenotype. Targeting these processes could offer a novel approach to prevent nephrolithiasis at its origin.